Production of tubular porous hydroxyapatite using electrophoretic deposition - Ustundag, Cem Bulent; Kaya, Figen; Kamitakahara, Masanobu; Kaya, Cengiz; Ioku, Koji (CERAMIC SOC JAPAN-NIPPON SERAMIKKUSU KYOKAI, 2012)
Hydroxyapatite (HA) ceramics have been recognized as bone substitute materials in orthopedic and dental applications because of their chemical and biological similarity to human bone. Porous HA ceramics can be used as scaffold materials, if their microstructure is controlled in terms of pore size and porosity. The objective of the present work was to produce tubular-shaped HA scaffolds for biomedical applications using the cost-effective technique of electrophoretic deposition (EPD) which enables various 3D shapes to be produced. Nano HA powders were produced and mixed with multi-walled carbon nanotubes (MWCNTs) by a hydrothermal process. Calcium acetate (Ca(CH3COO)(2)), and phosphoric acid (H3PO4) were used as starting materials for the synthesis of the nano HA powders. Porous HA coatings were deposited on carbon rods by EPD at 60 V using a butanol suspension mixture containing nano HA powders and MWCNTs. Nano composite coatings produced were sintered at 1200 C for 60 min to burn-out the carbon rod and MWCNTs. It was shown that MWCNTs provided crack-free coating layers after coating and a porous structure after sintering. The porous HA coatings obtained were coated using different EPD parameters in terms of applied voltage and deposition time. EPD provides a coating thickness of similar to 310 mu m for a deposition time of 480 s. This method enabled the formation of coatings with variable thickness, depending on the duration of coating and applied DC voltage. Hydrothermal mixing of HA/MWCNTs and the mechanism of deposition are also discussed. The methods can produce 3D-shaped HA scaffolds for clinical applications. The results demonstrate that the HA tubes obtained are candidate materials as scaffolds for bone repairing and generation. (C)2012 The Ceramic Society of Japan. All rights reserved.
Keywords: Hydroxyapatite; Porous; Scaffold; Carbon nanotube; Electrophoretic deposition; MECHANICAL-PROPERTIES; BONE-FORMATION; CERAMICS; SCAFFOLDS; OSTEOINDUCTION; COATINGS; POROSITY; Materials Science